Producción de una biopelícula a partir de las pectinas extraídas del mucílago de café (2021)
Coffee mucilage is an agro-industrial waste that generates a great environmental impact, therefore, the use of it in the production of biofilms represents an alternative to mitigate the effect caused by these wastes, as well as contributing to the reduction of plastics. conventional. This project aims to develop a proposal for the production of biofilms, from a 4% w / v concentration of pectin and glycerol to 1% w / v with a one-factor experimental design where films made from pectin are evaluated. citrus, compound pectin and mucilage pectin which was extracted by the selected method (acid hydrolysis), evaluating their physical and mechanical properties. Finally, according to the process carried out in the laboratory, the mass balance is carried out taking as a calculation basis 7425 Kg of mucilage / day, in order to describe the technical specifications and conditions of the process equipment, thus estimating the costs generated both in the extraction of pectin and in the production of biofilms.